2017
DOI: 10.1111/jpn.12691
|View full text |Cite
|
Sign up to set email alerts
|

Progressive resistance‐loaded voluntary wheel running increases hypertrophy and differentially affects muscle protein synthesis, ribosome biogenesis, and proteolytic markers in rat muscle

Abstract: Funding informationDiscretionary laboratory funds from JMW were provided to MDR as a subcontract to complete perform rat training studies. Laboratory start-up funds were also used by MDR to perform RNA and Western blotting analyses. SummaryWe examined if 6 weeks of progressive resistance-loaded voluntary wheel running in rats induced plantaris, soleus, and/or gastrocnemius hypertrophy and/or affected markers of translational efficiency, ribosome biogenesis, and markers of proteolysis. For 6 weeks, 8 male Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In rats, recent evidence suggests the degree of synergist ablation-induced plantaris hypertrophy parallels proportional increases in ribosome content ( Nakada et al, 2016 ). Our laboratory ( Mobley et al, 2016 , 2018b ; Roberts et al, 2016 ) and others ( West et al, 2016 ; Brook et al, 2017 ) have also reported that acute and chronic resistance exercise training models in rats increase indices of ribosome biogenesis and ribosome content, respectively.…”
Section: Training-induced Ribosome Biogenesis Is Greater In High Versmentioning
confidence: 68%
See 1 more Smart Citation
“…In rats, recent evidence suggests the degree of synergist ablation-induced plantaris hypertrophy parallels proportional increases in ribosome content ( Nakada et al, 2016 ). Our laboratory ( Mobley et al, 2016 , 2018b ; Roberts et al, 2016 ) and others ( West et al, 2016 ; Brook et al, 2017 ) have also reported that acute and chronic resistance exercise training models in rats increase indices of ribosome biogenesis and ribosome content, respectively.…”
Section: Training-induced Ribosome Biogenesis Is Greater In High Versmentioning
confidence: 68%
“…While mTORC1 is the hub that regulates MPS, there are multiple systems that regulate skeletal muscle proteolysis including ( Pasiakos and Carbone, 2014 ; Tipton et al, 2018 ): (a) the calcium-dependent calpain system which liberates myofibrillar proteins from sarcomeric Z-lines, (b) the autophagy-lysosomal system which degrades cellular organelles as well as myofibrillar proteins, (c) the caspase system which cleaves myofibrillar proteins into smaller fragments, and (d) the ubiquitin-proteasome system (UPS) which uses E1/E2/E3 enzymes to poly-ubiquinate myofibril fragments and degrade these proteins into individual amino acids via the 26S proteasome. Proteolysis rates are likely influenced by a combination of these systems, and several human and rodent studies have reported biomarkers in each system are dynamically altered in response to acute and chronic resistance exercise training ( Louis et al, 2007 ; Kerksick et al, 2010 , 2013 ; Dalbo et al, 2013 ; Kwon et al, 2015 ; Stefanetti et al, 2015 ; Mobley et al, 2018b ). Interestingly, rodent and in vitro studies have also demonstrated that inhibiting autophagy and UPS reduces skeletal muscle mass ( Masiero and Sandri, 2010 ) and promotes myotube atrophy ( Chandler et al, 2017 ), respectively, which suggests proteolytic mechanisms are seemingly obligatory for muscle mass maintenance.…”
Section: A Brief Overview Of Mechanisms That Facilitate Hypertrophy Imentioning
confidence: 99%
“…Numerous studies showed increased muscle mass after resistance running in mice. It has been reported that muscle mass is increased in the PLT (Legerlotz et al, 2008; Holland et al, 2016; Mobley et al, 2018), SOL (Konhilas et al, 2005; Legerlotz et al, 2008; Call et al, 2010; White et al, 2016), GAS (Mobley et al, 2018), m. quadriceps (Soffe et al, 2016), and TRI (Call et al, 2010) after long term (>4 weeks) resistance running. Our findings provide evidence of a potential molecular basis for the above findings as we report increased mTORC1 activation after one night of resistance running in the aforementioned muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as mouse handling and stress is minimal, the running wheel is considered an excellent model of physiological training with similar muscular adaptations as other well-accepted models such as synergistic ablation and electrical stimulation. Indeed, many groups have shown that voluntary resistance running leads to muscular hypertrophy in rodents (Legerlotz et al, 2008; Call et al, 2010; White et al, 2016; Mobley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, another possible explanation is that exercise increased overall cardiovascular and muscular fitness or reduced adipose tissue, rendering exercise dams more adept than sedentary dams in active coping behavior in FST2. Although these factors have not been explicitly studied in forced swim test, voluntary running in rats is beneficial for cardiovascular and skeletal muscle health (Pósa et al, 2015;Mobley et al, 2017) which may ultimately contribute to forced swim test performance. However, using body mass as a covariate still resulted in the main effect of exercise to reduce immobility in the FLX.…”
Section: Maternal Exercise Reduced Depressive-like Behaviour Whereas mentioning
confidence: 99%